Capsular tension ring alone and associated with acrylic foldable intraocular lens in posterior capsular opacification after phacoemulsification in dogs - Morales, Adriana [UNESP]; Costa, Paula Ferreira Da [UNESP]; Conceição, Luciano Fernandes Da [UNESP]; Andrade, Alexandre Lima De [UNESP]; Pádua, Ivan Ricardo Martinez [UNESP]; Marinho, Fábio Andrade [UNESP]; Brito, Fábio Luiz Da Cunha [UNESP]; Laus, José Luiz [UNESP] (Universidade Federal de Santa Maria, 2015)
The purpose of the study was to determine whether capsular tension ring (CTR) alone or associated with the implantation of an intraocular lens (IOL) could decrease the occurrence of posterior capsular opacification (PCO) after phacoemulsification cataract surgery in dogs. Twenty eyes of client-owned dogs with immature or mature cataracts were included in this study. In all the animals, any ophthalmic or systemic concurrent disease was excluded. The eyes were randomly selected to receive CTR alone or in association with the IOL. Laser flaremetry and clinical evaluations were conducted on post-operative days 2, 7, 14, 21 and 28. Fundus photographs were taken at the 28th and then every 30 days, up to 180 days. The results showed more inflammatory response on eyes with IOLs, although among the parameters evaluated, solely the synechiae showed significant statistical differences. Nevertheless, in both techniques almost no PCOs occurred at the end of the evaluations. These results suggest that the CTRs can be useful in the prevention of the post-operative capsular opacities, with minor complications

O objetivo do estudo foi determinar se o anel de tensão capsular (ATC), isoladamente ou associado à implantação de uma lente intraocular, poderia diminuir a ocorrência de opacificação da cápsula posterior (OCP) após a cirurgia de catarata por facoemulsificação em cães. Para tanto, cães portadores de catarata imatura ou madura foram avaliados, perfazendo um total de vinte olhos. Em todos os animais, foram excluídas quaisquer doenças oftálmicas e sistêmicas concomitantes. Os olhos foram selecionados aleatoriamente para receber o anel (ATC) isolado ou em associação com a lente. Flaremetria a laser e avaliações clínicas foram realizadas aos 2, 7, 14, 21, e 28 dias de pós-operatório. Fotografias foram tomadas aos 28 e a seguir a cada 30 dias, até os 180 dias. Os resultados mostraram inflamação mais importante nos olhos com IOL, embora, entre os parâmetros avaliados, apenas nas sinéquias houve diferença estatisticamente significativa. No entanto, em ambas as técnicas, quase nenhuma OCP ocorreu até o momento final das avaliações. Tais resultados sugerem que os anéis de tensão capsular (ATC) podem ser úteis na prevenção da opacidade capsular pós-operatória, sem complicações decorrentes
Anel de tensão capsular isolado e associado à lente intraocular acrílica dobrável na opacidade de cápsula posterior após facoemulsificação em cães
Keywords: Capsular tension ring; Cataract, dog; Intraocular lens; Posterior capsular opacification; Facoemulsification; Anel de tensão capsular; Catarata; Cães; Lente intraocular; Opacidade de cápsula posterior; Facoemulsificação